2016
DOI: 10.3906/sag-1504-77
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sebum configuration on Demodex spp. density

Abstract: Background/aim: Demodex spp. are ectoparasites living in the pilosebaceous units, which feed on the host's sebum and cellular proteins. The protective barrier of the skin consists of sebum secretion, moisture, and the acid mantle. In this study, we aimed to determine the effects of skin sebum, moisture, pH levels, and sebum configuration on Demodex spp. density Materials and methods: Forty-five patients who had demodicosis were enrolled in the study group, while the control group consisted of 40 subjects witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
0
20
0
3
Order By: Relevance
“…In our study, 58.9% of the participants with skin moisture less than 30%, 54.3% of with the skin moisture of 30–50%, and 50% of those having skin moisture higher than 50% are infested; however, the differences were not significant. In another study conducted in Turkey, it was found that the sebum and moisture quantities in the demodicosis group were lower than that of the control group, but the difference was also not significant . Participants with a skin pH of 5.1–6.5 were more infested than those with a pH of 4–5; however, the differences were not significant.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In our study, 58.9% of the participants with skin moisture less than 30%, 54.3% of with the skin moisture of 30–50%, and 50% of those having skin moisture higher than 50% are infested; however, the differences were not significant. In another study conducted in Turkey, it was found that the sebum and moisture quantities in the demodicosis group were lower than that of the control group, but the difference was also not significant . Participants with a skin pH of 5.1–6.5 were more infested than those with a pH of 4–5; however, the differences were not significant.…”
Section: Discussionmentioning
confidence: 88%
“…Participants with a skin pH of 5.1–6.5 were more infested than those with a pH of 4–5; however, the differences were not significant. Demirdag et al . reported that skin pH levels were significantly higher in the group with demodicosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Bununla birlikte cildin nem, pH ve sıcaklığı ile Demodex spp. arasındaki ilişkiye yönelik çok az sayıda çalışma mevcuttur (9)(10)(11)(12) Demodex spp. nin yüz bölgelerindeki dağılımına bakıldığında, enfestasyonun en fazla yanakta olduğu (toplam 1692 tane; ortalama 10,4/cm 2 ), bunu sırasıyla nazolabiyal (toplam 652 tane; ortalama 7,2/cm 2 ) ve çene (toplam 510 tane; ortalama 6,6/cm 2 ) bölgesinin izlediği görüldü.…”
Section: Introductionunclassified